Contrastive Analysis English Vowel Produced By Mandailing Speakers - Sausan Sabila; Afrahul Fadhillah Parinduri; Dedy Suhery; Rahmadsyah Rangkuti (Universitas Palangka Raya, 2026)
This study examines the acoustic production of English vowel contrasts by native Mandailing speakers through a sociophonetic lens, exploring how first-language background and gender shape pronunciation patterns. Data were collected via a reading task involving targeted English vowel pairs (/ɪ–iː/, /ʊ–uː/, /æ–e/, and /ʌ–uː/), which were recorded and acoustically analyzed using Praat software to measure first (F1) and second (F2) formant frequencies alongside vowel duration. The results demonstrate that while Mandailing speakers recognize distinct English vowel categories and attempt to separate them, they exhibit restricted vowel space and overlapping acoustic distributions compared to native standards. Notably, the male participant displayed reduced acoustic distance in tongue placement for front vowels and inverted duration patterns for back vowels. Conversely, the female speaker maintained more native-like vowel quality distinctions but showed reliance on adjusted temporal boundaries. These structured variations confirm that unfamiliar target language categories are dynamically integrated into the speaker's native phonological framework. Ultimately, the study highlights how entrenched regional speech practices and social variables actively systematicize non-native phonetic execution.